Circadian Functioning and Quality of Life in Substance Use Disorder Patients With and Without Comorbid Major Depressive Disorder - Hashemzadeh, Iman; Marquez-Arrico, Julia E.; Hashemzadeh, Kosar; Navarro, José Francisco; Adan, Ana (Frontiers in Psychiatry, 2021)
Aim: Although a relationship between circadian disruption and development of several psychiatric disorders, such as major depressive disorder (MDD) and substance use disorder (SUD), has been observed, knowledge on this area is scarce yet. Therefore, this study aims to analyze the circadian functioning and quality of life (QOL) in SUD patients with and without comorbid MDD, two highly prevalent clinical entities with difficult therapeutic management. Methods: One hundred sixty-three male patients under treatment, 81 with SUD and 82 with SUD comorbid major depressive disorder (SUD + MDD), were evaluated. For the circadian functioning assessment, we calculated Social Jet Lag (SJL) and used the reduced Morningness–Eveningness Questionnaire (rMEQ) and the Pittsburgh Sleep Quality Index (PSQI). QOL was measured using the shortened version of the World Health Organization's Quality of Life Questionnaire (WHOQOL-BREF). We collected sociodemographic and clinical variables to evaluate their possible influence on the circadian functioning. Intergroup differences among the variables were examined by different analyses of covariance (ANCOVA and MANCOVA). The possible relationships of quantitative clinical variables with rMEQ, PSQI, and WHOQOL-BREF were explored using bivariate correlation analysis. Results: Lower SJL appears in the SUD + MDD group compared with SUD. The intermediate-type was more prevalent in the SUD group, while a higher percentage of morning-type patients was found in the SUD + MDD. Sleep quality (including latency and daytime dysfunction) was worse for SUD + MDD patients than for SUD even after controlling age and age of SUD onset variables. Last, QOL was poorer in patients with SUD + MDD and, for them, psychological health had a negative relationship with SJL and severity of depression. Conclusions: Our data support and extend previous findings indicating that SUD + MDD is associated with worse clinical characteristics, more sleep problems, and poorer QOL than SUD patients. These results underline the importance of a precise assessment of these measurements in future studies conducted in SUD patients with/without MDD comorbidity that could be considered from a therapeutic point of view.